Corporatization and privatization lessons from New Zealand - Duncan, Ian 1950-; Bollard, Alan (Oxford Univ. Press, 1992)
The restructuring of New Zealand's public sector has had immediate and long-term economic implications, at the same time that changes in the regulatory structure have affected virtually every market. This book looks at one important facet of the restructuring: the commercialization of state trading departments under the State-Owned Enterprises Act 1986